PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN OPERATOR SPBU BEKASI PT PERTAMINA RETAIL - Bayu Setiawan; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this study was to determine the effect of work environment and work discipline on work productivity of employees at the Bekasi SPBU Operators Section, PT Pertamina Retail. The research method used is descriptive qualitative and quantitative analysis, the analysis model used linear regression either partially or simultaneous. The population in this study were 52 employees of the Bekasi SPBU Operator Section, Ahmad Yani. The sampling technique in this study used a saturated sampling technique, all members of the population were sampled totaling 52 employees. The result work environment and work discipline have a positive and significant effect on the work productivity of employees of PT Pertamina Retail's Bekasi SPBU Operators Section, either partially or simultaneous.